Opportunities and Challenges in Mastering Polysemous Words and Idioms in Foreign Language Learning Based on Analogous Procedures in the Native Language - Stakić, Mirjana M.; Arsić, Zvezdan M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The paper points out some of the potential problems in foreign language learning that may arise during the enrichment of one’s vocabulary with polysemous words and idioms (phrasemes). The aim is to analyse when exactly their acquisition should start in second language learning, as well as to indicate some of the methodological possibilities that allow for its realisation. Their acquisition requires consistency and continuity in the presentation of these lexical layers, and understanding—interpretation of contextual meaning. It is necessary to start enriching student vocabulary with such lexical layers in a timely manner. This timeliness means that the acquisition of such vocabulary and lexical layers should begin at an early age, in the very first stages of second language learning, and some methodological procedures, such as didactically guided play, allow for its realisation. Different types of games (imagination and drama games: pantomime, role-play, and dramatization), which can also be used to for modelling games in foreign language learning, and enriching student vocabulary with polysemous words and idioms, as well as creating an authentic context that allows students to understand the concept of figurative meaning in real-life language use, are presented on the examples of the Serbian language as the native language.
Keywords: foreign language learning; vocabulary enrichment; polysemous words; Serbian language; idioms; imagination and dramatization games